Pengaruh Penggunaan Metode (Mim-Mem) Mimicry Memorization terhadap Peningkatakan Kemampuan Menghafal Kosakata Bahasa Arab Siswa Kelas V MI Al-Mustawa Gunungsindur Bogor - Nur Azmi Laila; Sri Nurul Milla; Muhammad Fahri (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
One of the efforts that can be done to improve the quality of education is by updating the learning method. An education is said to be good if the teaching method used is the right method, this will make it easier to achieve a goal in learning. This study was conducted to determine whether there was a significant effect on improving the ability to memorize Arabic vocabulary for fifth grade students of MI Al-Mustawa Gunungsindur Bogor after the Mimicry Memorization (Mim-Mem) method was applied. This research is classified as quantitative research. With the experimental method and design